2008
DOI: 10.1620/tjem.215.23
|View full text |Cite
|
Sign up to set email alerts
|

Maternal and Neonatal Factors Associated with the High Yield of Mononuclear Low-Density/CD34+ Cells from Placental/Umbilical Cord Blood

Abstract: Placental/umbilical cord blood (CB) contains nucleated cells and hematopoietic stem/ progenitor cells (CD34 + cells). However it is difficult to predict the number of nucleated/ CD34 + cells in each CB before cell processing. Despite many previous studies from institutes affiliated with CB banks in metropolitan areas, little information is available regarding the characteristics of CB units from other medical facilities. The purpose of the present study was to analyze the maternal/neonatal factors on the yield… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
36
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(37 citation statements)
references
References 37 publications
1
36
0
Order By: Relevance
“…As described by others [16], [24], [26], maternal age had no impact on the HSPC concentration. In contrast, other groups reported an influence of maternal age on HSPC concentration, which is in line with our results [19], [27].…”
Section: Discussionsupporting
confidence: 69%
“…As described by others [16], [24], [26], maternal age had no impact on the HSPC concentration. In contrast, other groups reported an influence of maternal age on HSPC concentration, which is in line with our results [19], [27].…”
Section: Discussionsupporting
confidence: 69%
“…This also was in line with Surbek et al who reported that the CD34+ cell count per cord blood sample was independent of gestational age. On the other hand, Omori et al had found that total number of CD34+ cell had a reverse correlation with the gestational age. Mancinelli et al reported that gestational age of more than 39 weeks increases CD34 significantly.…”
Section: Discussionmentioning
confidence: 97%
“…Regarding maternal height, three articles show no correlation with TNC or CD34+ cell quantities in UCB. Concerning UCB volume, data seem controversial . Maternal weight on admission significantly influences CD34+ cells amount as shown in the study by Al‐Sweedan and coworkers, but not in the studies by Omori and coworkers .…”
Section: Highlighted Factorsmentioning
confidence: 95%
“…Concerning UCB volume, data seem controversial . Maternal weight on admission significantly influences CD34+ cells amount as shown in the study by Al‐Sweedan and coworkers, but not in the studies by Omori and coworkers . Concerning TNCs, the findings from all these articles are contradictory .…”
Section: Highlighted Factorsmentioning
confidence: 97%
See 1 more Smart Citation